2010
DOI: 10.1074/jbc.m110.105965
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Motif of CDK5RAP2 Mediates Its Localization to Centrosomes and the Golgi Complex

Abstract: As the primary microtubule-organizing centers, centrosomes require ␥-tubulin for microtubule nucleation and organization. Located in close vicinity to centrosomes, the Golgi complex is another microtubule-organizing organelle in interphase cells. CDK5RAP2 is a ␥-tubulin complex-binding protein and functions in ␥-tubulin attachment to centrosomes. In this study, we find that CDK5RAP2 localizes to the Golgi complex in an ATPand centrosome-dependent manner and associates with Golgi membranes independently of micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
120
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(131 citation statements)
references
References 48 publications
9
120
2
Order By: Relevance
“…CDKRAP2 and Cep192, human counterparts of CNN and Spd-2, also increase on centrosome maturation as does pericentrin, and the proteins show interdependency for the recruitment of g-tubulin (Haren et al 2009;Lee and Rhee 2011). In part, this reflects the physical association of g-tubulin with the amino-terminal part, and pericentrin with the carboxy-terminal part of CDKRAP2 (Fong et al 2008;Choi et al 2010;Wang et al 2010).…”
Section: Pcm Assemblymentioning
confidence: 99%
“…CDKRAP2 and Cep192, human counterparts of CNN and Spd-2, also increase on centrosome maturation as does pericentrin, and the proteins show interdependency for the recruitment of g-tubulin (Haren et al 2009;Lee and Rhee 2011). In part, this reflects the physical association of g-tubulin with the amino-terminal part, and pericentrin with the carboxy-terminal part of CDKRAP2 (Fong et al 2008;Choi et al 2010;Wang et al 2010).…”
Section: Pcm Assemblymentioning
confidence: 99%
“…We therefore investigated if Cnn is re--utilized in post--mitotic neurons in order to localize microtubule nucleation by an analogous anchoring process. The mammalian Cnn paralog CDK5RAP2 localizes to somatic Golgi during interphase in non--neuronal cells 33 . Moreover, in addition to their function in dendrite secretory trafficking 34,35 , Golgi outposts were recently identified as a site of acentrosomal microtubule nucleation in dendrites 20 .…”
Section: Cnn Localizes To One Side Of Manii--positive Golgi Outpostsmentioning
confidence: 99%
“…The function of the carboxy terminus is mostly unknown, although we have shown that loss of the SPD motif and carboxy terminus results in very low levels of truncated Cnn at the centrosome and in high levels at the metaphase plate (Eisman et al 2009). A recent study reported that a motif in the Cnn carboxy terminus is conserved in mouse CDK5RAP2 (Wang et al 2010), but a PsiBLAST with the D. melanogaster motif found minimal homology, with an E-value of 7.3 between fly and mouse. Clearly, future studies of Cnn are required to define the molecular basis of Cnn function.…”
Section: Discussionmentioning
confidence: 99%
“…C. Eisman and T. C. Kaufman carboxy terminus is conserved in mouse CDK5RAP2 (Wang et al 2010), but a PsiBLAST with the D. melanogaster motif found minimal homology, with an E-value of 7.3 between fly and mouse. Clearly, future studies of Cnn are required to define the molecular basis of Cnn function.…”
mentioning
confidence: 99%